The role of tumor acidification in aggressiveness, cell dissemination and treatment resistance of oral squamous cell carcinoma - Bem Prunes, Bianca de; Nunes, Júlia Silveira; da Silva, Viviane Palmeira; Laureano, Natalia K.; Gonçalves, Douglas Rodrigues; Machado, Ian Santana; Barbosa, Silvia; Lamers, Marcelo Lazzaron; Rados, Pantelis Varvaki; Kurth, Ina; Heß, Jochen; Jou, Adriana; et al. (Life sciences, 2021)
Aims - To investigate the role of tumor acidification in cell behavior, migration, and treatment resistance of oral squamous cell carcinoma (OSCC). - Main methods - The SCC4 and SCC25 cell lines were exposed to acidified (pH 6.8) cell culture medium for 7 days. Alternatively, a long-term acidosis was induced for 21 days. In addition, to mimic dynamic pH fluctuation of the tumor microenvironment, cells were reconditioned to neutral pH after experimental acidosis. This study assessed cell proliferation and viability by sulforhodamine B and flow cytometry. Individual and collective cell migration was analyzed by wound healing, time lapse, and transwell assays. Modifications of cell phenotype, EMT induction and stemness potential were investigated by qRT-PCR, western blot, and immunofluorescence. Finally, resistance to chemo- and radiotherapy of OSCC when exposed to acidified environmental conditions (pH 6.8) was determined. - Key findings - The exposure to an acidic microenvironment caused an initial reduction of OSCC cells viability, followed by an adaptation process. Acidic adapted cells acquired a mesenchymal-like phenotype along with increased migration and motility indexes. Moreover, tumoral extracellular acidity was capable to induce cellular stemness and to increase chemo- and radioresistance of oral cancer cells. - Significance - In summary, the results showed that the acidic microenvironment leads to a more aggressive and treatment resistant OSCC cell population.
Gesehen am 13.01.2022